Relationships between microstructure and micromechanical stresses on local pitting during galvanic corrosion in AA7050. (1st July 2019) - Nicolas, Andrea; Mello, Alberto W.; Sangid, Michael D.
Graphical abstract: Highlights: Corrosion of loaded AA7050 studied via combined mechanical and chemical analysis. Analysis is supported by high-resolution spatial characterizations and modeling. Cathodic particles show localized corrosion worsened by passive layer removal. Local corrosion is attributed to high stresses at the cathodic particles. Abstract: The mechanisms affecting localized stress corrosion in AA7050-T7451 were jointly investigated by spatially characterizing the microstructure, heterogeneous strains, and surface morphological evolution across the same region of interest for three specimens subjected to corrosion under loading. The experimental observations were used to infer local stresses relative to the microstructure via crystal plasticity modeling. The statistical relationships between corrosion and the micromechanical quantities were studied using Gaussian Process modeling. The results showed that highly-concentrated tensile stresses intensify corrosion at the particles, concluding that pitting is a confined chemical process strongly related to the high levels of axial stresses near microstructural features.